2015
DOI: 10.1590/1807-3107bor-2015.vol29.0097
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, feasibility and perceived satisfaction of the use of the Atraumatic Restorative Treatment approach for people with disability

Abstract: Unmet caries treatment need is prevalent among people with disability, partly due to difficulties cooperating with conventional dental treatment. This study compared Atraumatic Restorative Treatment (ART) with conventional restorative treatment (CRT) in the clinic and under general anaesthesia (GA), in terms of feasibility, acceptability and respondent satisfaction in patients referred for special care dentistry. Patients referred for dental restorative care were treated using either ART or CRT approach. Accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Suitability of the approaches was analysed in terms of acceptance, feasibility and level of satisfaction after one year of treatment, the results of which are published elsewhere. 7 Restorations were evaluated by two calibrated independent examiners at 6, 12, 24, 36 and 60 months using established ART restoration assessment criteria. 6 The inter-examiner consistency, expressed as kappa coefficient and the percentage of agreement (Po) at the 60 months evaluation was 0.84 (95%CI: 0.77-0.92) and 95% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suitability of the approaches was analysed in terms of acceptance, feasibility and level of satisfaction after one year of treatment, the results of which are published elsewhere. 7 Restorations were evaluated by two calibrated independent examiners at 6, 12, 24, 36 and 60 months using established ART restoration assessment criteria. 6 The inter-examiner consistency, expressed as kappa coefficient and the percentage of agreement (Po) at the 60 months evaluation was 0.84 (95%CI: 0.77-0.92) and 95% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5 The Atraumatic Restorative Treatment (ART) 6 approach has proven to be an acceptable, feasible and effective technique to prevent/restore cavities in this population. 7 Manual excavation reduces noise, anxiety and vibration by avoiding the use of rotary instruments and the use of a biological, less moisture-sensitive, high-viscosity glass-ionomer cement (HVGIC) makes ART an interesting alternative to conventional operative treatment. There is evidence that ART reduces the need for restorative care under general anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the survey among 195 dentists, Edwards and Marry demonstrated that physical barriers, lack of experience, lack of knowledge, and lack of facilities were common reasons for not offering dental care for special needs patients. Therefore, dental treatment for patients with special needs is often performed under general anesthesia usually in a hospital.…”
Section: Discussionmentioning
confidence: 99%
“…We need also to be the advocates of our patients who have the right to expect and demand equal options and outcomes–to bridge the gap between our patients and the dental profession. What could be more satisfying than empowering the patient to express his/her desires in terms of treatment processes and outcomes? Encouraging steps have been made in Ireland where the results of a Delphi panel survey which included people with disability, produced a list of prioritized goals for dental services for that target group …”
mentioning
confidence: 99%